The susceptibility to degradation of stone materials used in the built heritage of the Ortygia island (Syracuse, Italy): A laboratory study. (October 2021) - Belfiore, C.M.; Calabrò, C.; Ruffolo, S.A.; Ricca, M.; Török, Á.; Pezzino, A.; La Russa, M.F.
Abstract: Syracuse and the other cities of the Hyblaean area (in south-eastern Sicily) are characterized by a close relationship between building stone and geological context, since the wide use of local calcarenites characterized and defined their urban planning and architecture. In this paper, we discuss the results of a research aimed at investigating four types of limestone used in the built heritage of Ortygia, the historic city centre of Syracuse (in south-eastern Sicily). Specifically, the following carbonate stones have been investigated: 1) Syracuse limestone and 2) Melilli limestone, from the Monti Climiti Fm., 3) Oolitic limestone from the Monte Carrubba Fm., and 4) Giuggiulena limestone from the Pleistocene Panchina. All lithotypes underwent several mineralogical-petrographic and physical-mechanical investigations to individuate the causes responsible for their different durability when placed in the outdoor environment. Results obtained were also compared with literature data concerning the other two limestones employed as building and decorative materials in the façades of historic buildings in Ortygia, precisely the " Noto limestone" and the " Lumachelle limestone", previously studied by other authors. Results achieved are consistent with deterioration types macroscopically observed in the monuments, and highlight the close relationship between compositional, textural, physical and mechanical characteristics of the stone and its specific damage.